Practicing sectarianism : archival and ethnographic interventions on Lebanon - Deeb, Lara; Nalbantian, Tsolin; Sbaiti, Nadya (Stanford (Calif.) : Stanford University Press, 2023)
Practicing Sectarianism explores the imaginative and contradictory ways that people live sectarianism. The book's essays use the concept as an animating principle within a variety of sites across Lebanon and its diasporas and over a range of historical periods. With contributions from historians and anthropologists, this volume reveals the many ways sectarianism is used to exhibit, imagine, or contest power: What forms of affective pull does it have on people and communities? What epistemological work does it do as a concept? How does it function as a marker of social difference? Examining social interaction, each essay analyzes how people experience sectarianism, sometimes pushing back, sometimes evading it, sometimes deploying it strategically, to a variety of effects and consequences. The collection advances an understanding of sectarianism simultaneously constructed and experienced, a slippery and changeable concept with material effects. And even as the book's focus is Lebanon, its analysis fractures the association of sectarianism with the nation-state and suggests possibilities that can travel to other sites. Practicing Sectarianism, taken as a whole, argues that sectarianism can only be fully understood—and dismantled—if we first take it seriously as a practice. -- Présentation de l'éditeur.
Introduction. Practicing sectarianism in Lebanon / Lara Deeb, Tsolin Nalbantian, and Nadya Sbaiti -- No room for this story : education and the limits of sectarianism during the Mandate Era / Nadya Sbaiti -- Negotiating citizenship : Shi'i families and the Ja'fari shari'a courts / Linda Sayed -- The archive is burning : law, unknowability, and the curation of history / Maya Mikdashi -- Donating in the name of the nation : charity, sectarianism, and the Mahjar / Reem Bailony -- Along and beyond sect? : Olfactory aesthetics and Rum Orthodox identity / Roxana Maria Arãş -- From murder in New York To salvation from Beirut : Armenian intrasectarianism / Tsolin Nalbantian -- Inequality and identity : social class, urban space and sect / Joanne Randa Nucho -- When exposure is not enough : sectarianism as a response to mixed marriage / Lara Deeb.
Bibliogr. p. [219]-232, index, notes
Keywords: Communalism -- Lebanon; Sects -- Political aspects -- Lebanon; Sects -- Social aspects -- Lebanon; Lebanon -- Ethnic relations